Formulation and Characterization Self-Nanoemulsifying Drug Delivery Systems (SNEDDS) Chloroform Extract of Gaharu Leaves (Gyrinops verstegii (Gilg.) Domke - Siska Noviana Dewi; Ronny Martien; Laras Novitasari; Tri Rini Nuringtyas (Fakultas Farmasi Universitas Andalas, 2024)
Gaharu (Gyrinops versteegii (Gilg.) Domke) is a native Indonesian plant with many potential medicinal compounds. The compounds contained in the chloroform extract of gaharu leaves are mostly nonpolar terpenoids and fatty acids, so their solubility in water is low. Self-nanoemulsifying drugs delivery system (SNEDDS) technology can increase the solubility and bioavailability of drugs or active compounds in cells. This study aims to formulate and characterize SNEDDS from chloroform extract of gaharu leaves. The research began with the extraction of gaharu leaves by soxhletation. Formula optimization was carried out with various oils, surfactants, and cosurfactants. SNEDDS preparations were then characterized by testing particle size, polydispersity index, percent transmittance, and determining globule morphology. The optimal SNEDDS formula contained miglyol® 812N oil and Tween 80 (32%:68%) with particle size 63.25 ± 5.93 nm, polydispersity index 0.272 ± 0.016, and percent transmittance 98.33 ± 0.23%, spherical globule morphology. This study concluded that the optimal formula for SNEDDS chloroform extract of gaharu leaves (Gyrinops versteegii (Gilg.) Domke) had good physical characteristics. Keywords: Gyrinops verstegii (Gilg.) Domke; gaharu; SNEDDS gaharu; miglyol